Extrusion-based 3d freeze printing of multi-functional aerogels - Yang, Guang (Kansas State University, 2024)
Aerogels constitute a unique class of synthetic porous ultralight materials, derived from gels where the liquid component is substituted by gas while retaining the gel structure. Their outstanding material properties, including high porosity and low density, have spurred exploration across various domains such as catalysis, thermal insulation, solar energy utilization, piezoelectricity, energy storage, low-temperature glass formation, sensors, adsorption, and photocatalysis. The integration of 3D printing technology into aerogel production offers unprecedented design flexibility and the capacity to customize material characteristics. Nevertheless, prevailing 3D printing methods for aerogels encounter challenges concerning printability, microstructure regulation, and macrostructure manipulation. To tackle these obstacles, a novel 3D printing method known as 3D Freeze Printing (3DFP) has been developed internally, merging freeze casting with additive manufacturing techniques. This approach facilitates the precise fabrication of tailored geometries with controlled microporous structures. Previous investigations have primarily focused on a limited range of materials such as graphene and silver nanowires, necessitating exploration into diverse materials to unlock the full potential of 3DFP. Additionally, comparative evaluations between multifunctional aerogels produced via 3DFP and those from conventional methods remain unexplored. Former studies predominantly relied on optical imaging for 3DFP characterization, constraining insights into material deposition and solidification. Systematic analysis of the extrusion process and quantitative assessment pose considerable challenges but are crucial for optimizing 3DFP processes across industries like chemical, machinery, electronics, aerospace, and biomedical engineering. This thesis addresses these gaps by fundamentally studying the extrusion-based 3DFP method and its potential applications. After a comprehensive review of freeze casting and current extrusion-based 3D printing techniques, precedes investigations using X-ray synchrotron micro-radiography from leading facilities like the Advanced Photon Source and SLAC National Accelerator Laboratory are presented. These experiments provide real-time insights into material behavior during freeze casting and 3DFP processes. Moreover, the fabrication and characterization of novel cellulose nanocrystal (CNC) aerogels using 3DFP demonstrate exceptional acoustic absorption and mechanical properties tailored through freezing direction modification. These nano-cellulose aerogels present promising applications in ultra-lightweight sound absorption devices for aerospace use. Additionally, this thesis extends to extrusion-based 3D printing of zirconium carbide (ZrC) nuclear fuel cell structures, reporting the influence of additives like Nano Crystalline Cellulose (NCC) and Vanadium Carbide (VC) through rheological and mechanical testing. Integrating additive manufacturing with advanced materials like ZrC and tailored additives marks a significant stride towards sustainable propulsion systems for future space missions. In conclusion, this thesis delves into the fundamental aspects and practical applications of extrusion-based 3DFP, paving the way for optimized aerogel production across diverse industries and advancing materials science for futuristic technologies.
Keywords: 3D freeze printing; Multi-functional aerogels